Associations between serum triglycerides and abdominal aortic calcification in a cross-sectional study from the United States of America. (14th October 2021) - Penson, P; Javed, S; Banach, M; Lip, G Y H
Abstract: Background: Abdominal aortic calcification (AAC) has recently been recognised as a risk factor for cardiovascular disease, as it shares pathophysiological mechanisms with coronary artery disease. Purpose: We investigated relationships between AAC and traditional cardiovascular risk factors in a cross-sectional epidemiological cohort from the USA Methods: We used data from the National Health and Nutrition Evaluation Survey (NHANES) from the years 2103–2014. Dual-energy X-ray absorptiometry (DXA scans) were performed for a subset of 3140 NHANES participants over the age of 40. The images were scored according to ACC-24, a 24-point scale. We performed binary logistic regression to investigate relationships between demographic variables (age, sex, poverty income ratio, & educational status) CV risk factors (triglycerides (fasting, and non-fasting) LDL-C, HDL-C systolic blood pressure, body mass index, smoking status & diabetes) medicine use (statins, antihypertensives and antiplatelets) and AAC status (patients with a score ≥2 on the 24-point scale were considered AAC positive). Non normally-distributed variables were categorised for the purposes of analysis. Results: Participants with AAC were older (mean 65.5 years ± SD 11.7) than unaffected individuals (56.1±11.1) AAC was also associated with higher BMI (28.7±5.8 v. 27.6±4.8 kg/m 2 ), and higher systolic blood pressure (131.3±19.5 v 125.8±18.4 mmHg). We found a strong relationship between plasma triglyceride concentrations and AAC. In univariate analysis, fasting triglycerides above the first quartile were associated with approximately double the risk of AAC, compared to those in the first quartile (see table). This relationship persisted when the analysis was adjusted for demographics, risk factors and medicine use. A similar pattern was seen with non-fasting triglycerides (see table). Conclusions: We found a strong relationship between triglycerides and AAC. Further work is required to determine whether this observation can be validated in other cohorts, and whether interventions to reduce triglyceides can alter the progression of AAC. Funding Acknowledgement: Type of funding sources: None.